2022
DOI: 10.1186/s13619-022-00130-x
|View full text |Cite|
|
Sign up to set email alerts
|

Cilia regeneration requires an RNA splicing factor from the ciliary base

Abstract: Cilia are microtubule-based organelles projected from most eukaryotic cell surfaces performing cell motility and signaling. Several previously recognized non-ciliary proteins play crucial roles in cilium formation and function. Here, we provide additional evidence that the Caenorhabditis elegans RNA splicing factor PRP-8/PRPF8 regulates ciliogenesis and regeneration from the ciliary base. Live imaging of GFP knock-in animals reveals that the endogenous PRP-8 localizes in the nuclei and the ciliary base. A weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…RNA interference (RNAi) was carried out as in (Xu et al, 2022) (Xu and Ou, 2022). Designed target sequence for tbb-1 could be found in (Honda et al, 2017) (Honda et al, 2017), this target was proved to inhibit expression of tbb-1 efficiently.…”
Section: Methodsmentioning
confidence: 99%
“…RNA interference (RNAi) was carried out as in (Xu et al, 2022) (Xu and Ou, 2022). Designed target sequence for tbb-1 could be found in (Honda et al, 2017) (Honda et al, 2017), this target was proved to inhibit expression of tbb-1 efficiently.…”
Section: Methodsmentioning
confidence: 99%
“…Following publication of the original article(Xu and Ou 2022), it is reported that the supplement figure S1-S5 were missing from the article. Additional file 1: Fig.S1contains only figure legends but no figures.The original article (Xu and Ou 2022) has been corrected.…”
mentioning
confidence: 99%
“…Following publication of the original article (Xu and Ou 2022 ), it is reported that the supplement figure S1-S5 were missing from the article. Additional file 1: Fig.…”
mentioning
confidence: 99%